The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/jclp.20754
|View full text |Cite
|
Sign up to set email alerts
|

Expectations

Abstract: Patients' expectations have long been considered a contributory factor to successful psychotherapy. Expectations come in different guises, with outcome expectations centered on prognostic beliefs about the consequences of engaging in treatment. In this article, we define outcome expectations and present assessment methods and clinical examples of outcome expectations. Our research review includes a comprehensive meta-analysis (N =8,016 patients across 46 independent samples) of the association between prethera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
253
3
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(305 citation statements)
references
References 26 publications
15
253
3
12
Order By: Relevance
“…Both psychotherapy outcome expectancy and treatment credibility are shown to be positively related to treatment outcomes (Constantino, Arnkoff, Glass, Ametrano, & Smith, 2011; Taylor, 2003). With regard to EMDR specifically, previous authors have asserted the view that beneficial effects of the treatment are incidental and might be explained by credibility, expectation for improvement, experimental demand, therapist enthusiasm, and therapist allegiance (Devilly, 2005; Herbert et al, 2000; Lohr et al, 1992; Lohr, Lilienfeld, Tolin, & Herbert, 1999).…”
mentioning
confidence: 99%
“…Both psychotherapy outcome expectancy and treatment credibility are shown to be positively related to treatment outcomes (Constantino, Arnkoff, Glass, Ametrano, & Smith, 2011; Taylor, 2003). With regard to EMDR specifically, previous authors have asserted the view that beneficial effects of the treatment are incidental and might be explained by credibility, expectation for improvement, experimental demand, therapist enthusiasm, and therapist allegiance (Devilly, 2005; Herbert et al, 2000; Lohr et al, 1992; Lohr, Lilienfeld, Tolin, & Herbert, 1999).…”
mentioning
confidence: 99%
“…Usually treatment expectations are assessed in psychotherapy by asking about the potential gain or the expected negative effects of the therapy [14]. The positive treatment expectations of a patient lead to a higher perception of self-efficacy and this, in turn, has a positive effect on the patient's motivation [15].…”
Section: Methods Study Objectives and Designmentioning
confidence: 99%
“…The positive treatment expectations of a patient lead to a higher perception of self-efficacy and this, in turn, has a positive effect on the patient's motivation [15]. In a meta-analysis, Constantino et al [14] reported a small (d=0.24) but significant positive effect of treatment expectations before therapy start on the treatment result, which means the more positive the expectations of a therapy are at the beginning, the more likely patients are to show an improvement at the end of treatment. This relationship appears to exist for various anxiety disorders (e.g.…”
Section: Methods Study Objectives and Designmentioning
confidence: 99%
“…estos estudios incluyen variables tales como el sexo (Mahalik, good y englar-carlson, 2003), la edad (swift y greenberg, 2012), la pertenencia a minorías étnicas (trujillo, 2008;Wang, 2007), el nivel socioeconómico (Nse) (swift y greenberg, 2012; Wierzbicki y pekarik, 1993;Williams Ketring, y salts, 2005), las expectativas sobre la psicoterapia (constantino, arnkoff, glass, ametrano, y smith, 2011;Davis, lebow, y sprenkle, 2012;Vogel y Wester, 2003), las emociones negativas asociadas a psicoterapia tales como el miedo y la vergüenza (corrigan, 2004;MacKenzie, gekoski, y Knox, 2006;Vogel y Wester, 2003;Yap, Wright, y Jorm, 2011) y el temor a ser estigmatizado como paciente de salud mental (lannin, guyll, Vogel, y Madon, 2013).…”
unclassified